Reticulated Platelets Predict Cardiovascular Death and Adverse Events in Coronary Artery Disease: A Systematic Review and Meta-analysis - Bongiovanni, Dario; Novelli, Laura; Condello, Francesco; Kirmes, Kilian; Han, Jiaying; Wein, Bastian; Elvinger, Sébastien; Viggiani, Giacomo; von Scheidt, Moritz; Laugwitz, Karl-Ludwig; Raake, Philip W.J.; Kastrati, Adnan; Chiarito, Mauro; Bernlochner, Isabell (Thrombosis and Haemostasis, 2023)
Background The pro-thrombotic immature or reticulated platelets (RPs) are known to be elevated in high-risk patients and in different pathological settings. It has been shown that RPs correlate with an insufficient antiplatelet response to antiplatelet agents. RPs are emerging novel predictors of adverse cardiovascular events in cardiovascular disease. This study, using the totality of existing evidence, evaluated the prognostic role of RPs in patients with coronary artery disease.Methods We performed a systematic review and meta-analysis including trials of acute and chronic coronary syndrome reporting clinical outcomes according to RPs levels in the peripheral blood. We compared patients with elevated RPs (RPshigh) to patients without elevated RPs (RPslow). Odds ratios (ORs) and 95% CIs were used as metric of choice for treatment effects with random-effects models. The primary endpoint was major adverse cardiovascular and cerebrovascular events (MACCE). Secondary endpoints were cardiovascular death, myocardial infarction, ischemic stroke, urgent coronary revascularization and bleedings.Results A total of 7 studies, including 2213 patients, were included. The risk for MACCE was significantly higher in RPshigh compared to RPslow patients (OR 2.67 [1.87; 3.81], I2 = 43.8%). RPshigh were associated with cardiovascular death (OR 2.09 [1.36; 3.22], I2 = 40.4%). No associations for RPshigh were detected with the other singular components of MACCE: myocardial infarction (OR 1.73 [0.89; 3.38] I2 = 60.5%) and stroke (OR 1.72 [0.59; 4.96] I2 = 21%). The risk of bleeding did not differ between groups(OR 0.58 [0.15; 2.22] I2 = 86.1%).Conclusion Elevated RPs are significantly associated with increased risk of cardiovascular events and cardiovascular death.
Keywords: ACS; immature platelets; immature platelet fraction; IPF; reticulated platelets; CCS; biomarker